LABORATORY BIOMARKERS TO FACILITATE DIFFERENTIAL DIAGNOSIS BETWEEN MEASLES AND KAWASAKI DISEASE IN A PEDIATRIC EMERGENCY ROOM: A RETROSPECTIVE STUDY - Danilo Buonsenso; Giulia Macchiarulo; Maria Chiara Supino; Francesco La Penna; Simona Scateni; Alessandra Marchesi; Antonino Reale; Elena Boccuzzi (Mediterranean Journal of Hematology and Infectious Diseases)
This retrospective study was conducted to analyze clinical and laboratoristic parameters to individuate specific differences and facilitate differential diagnosis between Measles and Kawasaki Disease (KD) at first evaluation in a emergency room. We found similar clinical features as duration of fever and number of KD criteria (p >0.5) but significant differences in white blood cell count, neutrophils, CRP and LDH levels (p < 0.001). LDH value ≥ 800 mg/dl had sensibility of 89% and specificity of 90% for Measles while CRP ≥ 3 mg/dl had sensibility 89% and specificity of 85% for KD. The combined use of CRP, LDH and AST showed accuracy of 86.67%.